Highlighting the Female Perspective in British Historical Drama: An Analysis of the Portrayal of Women Characters, Specifically Guinevere and Morgan Le Fay, in the Arthurian Legend - Racquel Fred Dalton (Studies in Social Science & Humanities, 2023)
This comprehensive analysis thoroughly explores the nuanced portrayal of female characters in British historical drama, focusing on the iconic figures of Guinevere and Morgan Le Fay within the Arthurian Legend. Tracing the evolution of these characters across medieval literature and contemporary historical dramas, the study examines the historical context, thematic intricacies, and reception dynamics that have shaped and reshaped their roles. Through a comparative lens, the paper contrasts the portrayals of Guinevere and Morgan Le Fay, unraveling shared commonalities, divergent paths, and their contributions to the narrative richness of Arthurian historical dramas. The exploration navigates the socio-cultural transformations reflected in these portrayals, emphasizing the significance of highlighting the female perspective in the enduring tapestry of British historical drama.